Effects of oral supplementation of β -hydroxy-β -methylbutyrate on muscle mass and strength in individuals over the age of 50: a meta-analysis - Li, Nan; Chen, Shanbin; He, Yuxi; Chen, Yamin; Duan, Xiaosa; He, Wenxing; Wang, Qihe; Liu, Sana; Liu, Tongbo; Fang, Haiqin (Frontiers in Nutrition, 2025)
Backgroundβ-Hydroxy β-Methylbutyrate (HMB) has shown potential in improving muscle protein turnover, which may be important for preventing muscle degradation in aging populations. The aim of this meta-analysis is to clarify the impact of HMB oral supplementation on muscle-related indicators and discover the interaction between dosage and duration. The findings will provide a scientific basis for the use of HMB oral supplementation in the management of muscle attenuation.MethodsA computer systems-based search for articles of randomized controlled trial (RCT) in the PubMed, Cochrane Library, Web of Science, ScienceDirect, EBSCO English databases and China Journal Full-Text Database (CNKI), Wan Fang Chinese databases, was conducted up to October 2023. Data were pooled using weighted mean difference (WMD) and 95% confidence intervals (95% CI).ResultsA total of 21 RCTs were included, involving 1935 participants, all of them were > 50 years old. Results showed a positive impact of HMB oral supplementation in improving muscle mass (appendicular skeletal muscle mass: WMD = 1.56 kg, 95% CI: 0.03–3.09 kg and lean mass: WMD = 0.28 kg, 95% CI: 0.16–0.41 kg), strength (handgrip strength: WMD = 0.54 kg, 95% CI: 0.04–1.04 kg and five-time chair stand test: WMD = –0.73 s, 95% CI: –1.35, –0.11 s), and physical function (gait speed: WMD = 0.06 m/s, 95% CI: 0.01–0.10 m/s). Subgroup analysis revealed that the effect of a dosage of 3 g/d had significant improvement, and the effect of supplementation duration lasting > 12 weeks had significant improvement, and a dosage of 3g/day for more than 12 weeks was recommended.ConclusionHMB oral supplementation can improve muscle mass, strength, and physical function. We recommend to implement supplementation at a dosage of 3 g for a duration exceeding 12 weeks to achieve optimal benefits.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/login, identifier 42024518958.